Iklan Penebangan Hutan - muhamad safi'i muhamad safi'i (Jurnal Sistem Informasi dan Teknologi Informasi, 2023)
Forests can be used for various human purposes, such as tree trunks that can be used as raw materials for making houses, leaves can be used as medicine, logs can be used as raw materials for making paper, and many more. Forest is a large land that is dominated by trees and hundreds of different plants. Forests are very important for human life and other creatures. Forests account for 75% of the production of the earth's biosphere and contain 80% of the earth's plant biomass and also produce a lot of oxygen for living things in the vicinity.Technology can be a means as an intermediary to protect the forest through the media in the form of animation. Animated advertisements can provide information on the importance of conserving forests for living things. In making animated videos designed using the ibispaintx, flipaclip and capcut applications. Ibispaintx is designed to create sketches or early animated drawings. Flipaclip is used to merge images that have been created from ibispaintx. While the capcut application is used to unite audio and video to make it a public service advertisement in the form of animation.